2022
DOI: 10.3390/pathogens11020153
|View full text |Cite
|
Sign up to set email alerts
|

Canine Staphylococcus argenteus: Case Report from The Netherlands

Abstract: Staphylococcus argenteus has been reported worldwide in humans, while reported non-human cases are sparse. Its complete epidemiology, alongside its infectivity and pathogenicity in humans and non-humans, remain to be clarified. Here, we describe the first reported canine Staphylococcus argenteus, causing a deep wound infection in a Labrador retriever after orthopedic surgery. The closed genome is reported, with phylogenic and genetic analyses, as well as extensive phenotypic antimicrobial susceptibility testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Today, it is suggested to use fosfomycin for the management of UTIs, particularly in severe UTIs in women and MDR Enterobacteriaceae [12,38,39]. Fosfomycin is an intensely efective drug against the uropathogenic MDR Enterobacteriaceae [40,41].We must be aware that due to the wide spreading of resistant Enterobacteriaceae isolates to antibiotics in diferent places (animals, humans, food, and environment), as well as fosfomycin usage in veterinarians, Enterobacteriaceae is readily transferred to new places and other bacteria [30,42]. Furthermore, considering the determinant locations of mobile genetic elements (for example, plasmids), even the minor recognized resistance cases are important.…”
Section: Discussionmentioning
confidence: 99%
“…Today, it is suggested to use fosfomycin for the management of UTIs, particularly in severe UTIs in women and MDR Enterobacteriaceae [12,38,39]. Fosfomycin is an intensely efective drug against the uropathogenic MDR Enterobacteriaceae [40,41].We must be aware that due to the wide spreading of resistant Enterobacteriaceae isolates to antibiotics in diferent places (animals, humans, food, and environment), as well as fosfomycin usage in veterinarians, Enterobacteriaceae is readily transferred to new places and other bacteria [30,42]. Furthermore, considering the determinant locations of mobile genetic elements (for example, plasmids), even the minor recognized resistance cases are important.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, bushmeat could actually be a possible source of contamination and spreading of such novel species, deserving investigation in the near future. Conversely, S. argenteus, known for its ability to cause various pathological conditions in humans (e.g., sepsis, joint infection, endocarditis, and lymphadenitis) (Chantratita et al, 2016;Jiang et al, 2018;Ohnishi et al, 2018;Hirai et al, 2022) and animals (e.g., abscess, wound infection, and bovine mastitis) (Indrawattana et al, 2019;Pumipuntu et al, 2019;Meijer et al, 2022), is being reported from food, and it is increasingly recognized as an emerging foodborne pathogen (Shi and Zhang, 2018;Fusco et al, 2020), being able to cause staphylococcal food poisoning due to the production of enterotoxins, as assessed in three outbreaks reported so far in Japan (Suzuki et al, 2017; Frontiers in Food Science and Technology frontiersin.org ). Although the actual prevalence and distribution of S. argenteus in food products and food-related environments is still unclear (Shi and Zhang, 2018), S. argenteus has been recently reported from different food sources, including RTE food, comprising those involved in food poisoning, as well as contact surfaces of kitchen utensils and specimens from food handlers (Table 3).…”
Section: Strategies Using Physical Methodsmentioning
confidence: 99%
“…To date, S. argenteus has been found in both humans and animals from many regions of the world, including Thailand [21,29]. Although S. argenteus has been identified in dairy cows [18,30], rabbits [31], canine [22], and pigs [32], its prevalence in wildlife is understudied.…”
Section: Comparing the Thailand Non-human Primate Carriage With Previ...mentioning
confidence: 99%
“…Recently, a number of clinical reports of S. argenteus, causing a disease similar to that of S. aureus, in both humans and animals has increased [21,22]. This study aimed to investigate the prevalence of S. aureus and S. argenteus carriage in buccal swab samples from wild long-tailed macaques (M. fascicularis) at KFP, Thailand.…”
Section: Introductionmentioning
confidence: 99%